Banlieue Nord: A Brief Contribution to How We Inhabit the North and How the North Inhabits Us - Gudd, Lena; Pons Braley, Antonin (Nordlit, 2020)
Beyond its many simplified representations such as cold, hostile, uninhabited, or unknown, the north reveals itself as a complex and multiple space of interwoven geographical, cultural, social, and conceptual dimensions. Influenced by world views, the power of maps and myths as well as the very relation to the landscape itself as one of extraction or attraction, humans subjectively apprehend these multiple norths. By dwelling in the northern lands through experience or imagination, ‘southerners’ and ‘northerners’ alike do not simply inhabit the north; they are in turn inhabited by it. Situated at the ‘gates of the north’ in subarctic Canada, the mono-industrial company town Fermont fits its town centre entirely under a single roof. Planned and commissioned in the 1970s by a mining company, the town’s Utopian purpose was to ‘make a society’ in an inhospitable climate, while serving the exploitation of the mine. Fermont’s case serves here as a laboratory to understand the complexities of the north in more general terms. At the crossroads of image-based practices and the humanities, this contribution engages with the question of how humans inhabit the north and how they are inhabited by it.